The woman in black - Hill, Susan, 1942- (New York : Vintage Books, 2011)
London solicitor Arthur Kipps ends up settling more than just typical estate business for a client when he is haunted by a series of terrifying sounds and images, including a ghostly woman dressed all in black, during his business trip.
"Soon to be a major motion picture starring Daniel Radcliffe"--Cover.
Originally published: Boston: D.R. Godine, 1983.
Young Adult
Young Adult
Keywords: Attorney and client -- Fiction; Ghost stories; Legal stories; England -- Fiction; England -- Fiction; Ghost stories; Legal stories